2014
DOI: 10.1177/1470320313515036
|View full text |Cite
|
Sign up to set email alerts
|

ACE insertion/deletion polymorphism (rs1799752) modifies the renoprotective effect of renin-angiotensin system blockade in patients with IgA nephropathy

Abstract: Introduction:Little is known about genetic predictors that modify the renoprotective effect of renin-angiotensin system (RAS) blockade in IgA nephropathy (IgAN). Materials and methods:The present multicenter retrospective observational study examined effect modification between RAS blockade and three RAS-related gene polymorphisms in 237 IgAN patients, including ACE I/D (rs1799752), AT1R A1166C (rs5186) and AGT T704C (rs699). Results: During 9.9 ± 4.2 years of observation, 63 patients progressed to a 50% incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…[25][26][27] However, some studies in Chinese and Japanese have found there was no association between IgAN and AGT. 28,29 In 2012, Kidney Disease Improving Global Outcomes introduced the clinical practice guidelines for IgAN suggesting that RAS blockade is listed as the cornerstone of therapy for IgAN. JUN and FOS are part of the transcription factor AP-1, which regulates the expression of genes involved in proliferation, cell death, differentiation, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] However, some studies in Chinese and Japanese have found there was no association between IgAN and AGT. 28,29 In 2012, Kidney Disease Improving Global Outcomes introduced the clinical practice guidelines for IgAN suggesting that RAS blockade is listed as the cornerstone of therapy for IgAN. JUN and FOS are part of the transcription factor AP-1, which regulates the expression of genes involved in proliferation, cell death, differentiation, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Teranishi et al . reported that an I/D polymorphism in ACE contributes to variability in intrarenal angiotensin II activity . Importantly, intrarenal angiotensin II activity reflects urinary AGT, associated with increased risk for renal dysfunction in obesity and metabolic syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Teranishi et al reported that an I/D polymorphism in ACE contributes to variability in intrarenal angiotensin II activity. 29 Importantly, intrarenal angiotensin II activity reflects urinary AGT, associated with increased risk for renal dysfunction in obesity and metabolic syndrome. 30 The ACE I/D genotypes may have an association with the urinary excretion of AGT, an index of intrarenal angiotensin II status, and may be predictors for the risk of renal dysfunction in glucocorticoid-induced obesity and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects are promoted by concomitant dietary sodium and phosphate restriction. In addition, the efficacy of RAS blockade could be modified by ACE (I/D) gene polymorphisms such that, in the future, personalized medicine could be developed using pharmacogenomics data 24 .…”
Section: Treatmentmentioning
confidence: 99%